2022
DOI: 10.1186/s12916-022-02564-1
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil degranulation and severely impaired extracellular trap formation at the basis of susceptibility to infections of hemodialysis patients

Abstract: Background Chronic kidney disease patients are at increased risk of mortality with cardiovascular diseases and infections as the two leading causes of death for end-stage kidney disease treated with hemodialysis (HD). Mortality from bacterial infections in HD patients is estimated to be 100–1000 times higher than in the healthy population. Methods We comprehensively characterized highly pure circulating neutrophils from HD and healthy donors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…Some authors observed increased NETs production by neutrophils isolated from dialysis patients upon phorbol-12-myristate-13-acetate (PMA) stimulation, 148,149 along with increased PAD4 levels in serum 149 or increased NE activity in both resting and PMA-stimulated neutrophils. 148 In contrast, others reported a decreased NETs formation capacity of isolated neutrophils from dialysis patients upon stimulation with PMA, lipopolysaccharide, or the Ca 2+ ionophore A23187 compared with healthy controls 15 (Table 2). The latter was observed along with a reduced PAD4 expression in neutrophils as well as a reduced capacity of agonist-induced ROS production, a decreased basal cellular content of the neutrophil granule proteins myeloperoxidase, NE, and MMP-9 (matrix metallopeptidase-9) but an increased surface expression of activation and degranulation markers (CD66b, CD15, CD18) by isolated neutrophils.…”
Section: Compendium On Increased Risk Of Cardiovascular Complications...mentioning
confidence: 93%
See 4 more Smart Citations
“…Some authors observed increased NETs production by neutrophils isolated from dialysis patients upon phorbol-12-myristate-13-acetate (PMA) stimulation, 148,149 along with increased PAD4 levels in serum 149 or increased NE activity in both resting and PMA-stimulated neutrophils. 148 In contrast, others reported a decreased NETs formation capacity of isolated neutrophils from dialysis patients upon stimulation with PMA, lipopolysaccharide, or the Ca 2+ ionophore A23187 compared with healthy controls 15 (Table 2). The latter was observed along with a reduced PAD4 expression in neutrophils as well as a reduced capacity of agonist-induced ROS production, a decreased basal cellular content of the neutrophil granule proteins myeloperoxidase, NE, and MMP-9 (matrix metallopeptidase-9) but an increased surface expression of activation and degranulation markers (CD66b, CD15, CD18) by isolated neutrophils.…”
Section: Compendium On Increased Risk Of Cardiovascular Complications...mentioning
confidence: 93%
“…Based on these latter findings, it was suggested that neutrophils from hemodialysis patients have a constant potent immune activation, which leads to substantial neutrophil degranulation, a subsequent limited preservation of degranulation capacity and a malfunctioning ROS cascade, and thereby a reduction in both NADPH oxidase-dependent and NADPH oxidase-independent NET formation. 15 Another study also concluded on an increased basal activation of neutrophils in hemodialysis patients upon observation of increased NETs formation, ROS production, surface activation marker expression, and H3cit levels by unstimulated neutrophils when isolated from hemodialysis patients compared to controls, along with a reduced fold-upregulation of NET formation upon neutrophil stimulation with PMA 135 (Table 2). Overall, reasons for the divergent findings on NETs formation capacity of neutrophils isolated from dialysis patients (being either increased or decreased upon PMA stimulation) remain currently unclear.…”
Section: Neutrophils and Nets As Contributors To Thrombotic Risk In Ckd?mentioning
confidence: 98%
See 3 more Smart Citations